2013
DOI: 10.1021/ol401012u
|View full text |Cite
|
Sign up to set email alerts
|

Photochromism of a Naphthalene-Bridged Imidazole Dimer Constrained to the “Anti” Conformation

Abstract: Anti-1,8-bisTPI-naphthalene in which two imidazole rings are constrained to an anti-conformation leading to the first-formed 1,4'-isomer of the bridged imidazole dimer has been synthesized. The color of the radicals is different from that of the previously reported bridged-imidazolyl radicals because the intramolecular interaction between the radicals becomes weak due to the anti-conformation. This molecular design would be a profitable strategy to control the color of the radicals of the bridged imidazole dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
(9 reference statements)
1
19
0
Order By: Relevance
“…The ns transient absorption experiment shows that the colored species of bisDMDPI-BP has a weak and broad background at 4700 nm, where the absorption band due to the radical-radical interaction was observed in the previously studied bridged imidazole dimers. 20,21,26 Our previous work demonstrated that the absorption band due to the radical-radical interaction decreases, becomes broad, and shifts to longer wavelengths with decreasing radical-radical interactions. 21 Since bisDMDPI-BP has little transient absorption at 4700 nm as compared to that of reported bridged imidazole dimers, 20,21 it indicates that the radical-radical interaction of the colored species of bisDMDPI-BP is weak because of the large dihedral angle of the bridging biphenyl.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ns transient absorption experiment shows that the colored species of bisDMDPI-BP has a weak and broad background at 4700 nm, where the absorption band due to the radical-radical interaction was observed in the previously studied bridged imidazole dimers. 20,21,26 Our previous work demonstrated that the absorption band due to the radical-radical interaction decreases, becomes broad, and shifts to longer wavelengths with decreasing radical-radical interactions. 21 Since bisDMDPI-BP has little transient absorption at 4700 nm as compared to that of reported bridged imidazole dimers, 20,21 it indicates that the radical-radical interaction of the colored species of bisDMDPI-BP is weak because of the large dihedral angle of the bridging biphenyl.…”
mentioning
confidence: 99%
“…BisDMDPI-BP is the 2,2 0 -isomer, in which the C-C bond is formed between the 2-position of an imidazole ring and the 2 0 -position of the other imidazole ring, 24 while almost all reported bridged imidazole dimers are the 1,2 0 -or the 1,4 0 -isomers, in which a C-N bond is formed between the two imidazole rings. 18,20,21,26 While there are several reports on the 2,2 0 -isomers of hexaarylbiimidazole (HABI) derivatives, 27,28 they are sensitive to temperature and pressure, and easily converted to the photochromic 1,2 0 -isomers via the imidazolyl radical formed by thermochromism or piezochromism. Therefore, the stable 2,2 0 -isomer of bisDMDPI-BP offers a unique opportunity to reveal the photochromism of a representative 2,2 0 -isomer.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Inspired by the photochromism of HABI, we have developed the bridged imidazole dimers to accelerate the thermal back reaction. [6][7][8][9][10][11][12][13][14][15][16][17] The bridged imidazole dimers show instantaneous coloration upon UV light irradiation and rapid fading in the dark. The half-lives of the colored species of the naphthalene-bridged imidazole dimer and the [2.2]paracyclophane-bridged imidazole dimer are 830 and 33 ms at 25 1C in benzene, respectively.…”
mentioning
confidence: 99%
“…The half-lives of the colored species of the naphthalene-bridged imidazole dimer and the [2.2]paracyclophane-bridged imidazole dimer are 830 and 33 ms at 25 1C in benzene, respectively. 8,16,17 Such fast photochromic molecules could serve as excellent probes and triggers to reveal and control phenomena which occur in the time scales within a few tens of ms.The fast photochromic molecules have potential for applications such as a holographic display and fluorescence switching. [18][19][20] We have broadened the photochromic properties such as the halflife and the color of the colored species by rational design of the bridged imidazole dimers.…”
mentioning
confidence: 99%
“…The naphthalene moiety is an ideal fluorophore, and its derivatives have been widely applied as fluorescent dyes, metal sensors, optical sensors and organic light-emitting materials because of their high absorption coefficients, high fluorescence and quantum yields, large Stokes shifts, good photostability and easy modification [6][7][8][9]. In recent years, naphthalimide-based probes have been developed to detect H + , Hg 2+ , Zn 2+ , Cu 2+ , Ag + , Cd 2+ , Pd 2+ , Cr 3+ , Al 3+ , Fe 3+ , and F -via chromogenic and fluorogenic analyses [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%